1998
DOI: 10.1152/ajpgi.1998.275.3.g564
|View full text |Cite
|
Sign up to set email alerts
|

Enteroinvasive bacteria directly activate expression of iNOS and NO production in human colon epithelial cells

Abstract: In these studies, we investigated whether bacterial infection of human colon epithelial cells is a sufficient stimulus to upregulate epithelial cell expression of inducible nitric oxide synthase (iNOS) and nitric oxide (NO) production. Human colon epithelial cells (Caco-2 and HT-29) rapidly upregulated iNOS mRNA and protein expression and NO production after infection with enteroinvasive Escherichia coli, Salmonella dublin, or Shigella flexneri but not after infection with noninvasive E. coli or an invasion-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
101
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 46 publications
6
101
2
Order By: Relevance
“…Because (28), epithelial-derived NO may also function in an antimicrobial role against enteric bacteria. This hypothesis is supported by studies in which enteroinvasive bacteria induce iNOS expression by cultured epithelial cells (59), similar to the effects of several proinflammatory cytokines (28). Moreover, we recently demonstrated that iNOS is strongly induced on colonic epithelial cells in mice infected with the gram-negative bacterial pathogen Citrobacter rodentium, a mouse-adapted version of enteropathogenic Escherichia coli.…”
Section: Discussionsupporting
confidence: 54%
“…Because (28), epithelial-derived NO may also function in an antimicrobial role against enteric bacteria. This hypothesis is supported by studies in which enteroinvasive bacteria induce iNOS expression by cultured epithelial cells (59), similar to the effects of several proinflammatory cytokines (28). Moreover, we recently demonstrated that iNOS is strongly induced on colonic epithelial cells in mice infected with the gram-negative bacterial pathogen Citrobacter rodentium, a mouse-adapted version of enteropathogenic Escherichia coli.…”
Section: Discussionsupporting
confidence: 54%
“…NO is produced enzymatically from arginine through the action of NO synthase (NOS) 4 , which exists in three isoforms, neuronal NOS (NOS1), inducible NOS (iNOS; NOS2), and endothelial NOS (NOS3). In many cell types, the expression of iNOS is inducible by cytokines and microbial products, and iNOS is the major NOS isoform expressed by intestinal epithelial cells (21,22). Expression of iNOS in these cells can either be constitutive, as in mouse ileum (23) and isolated normal human duodenocytes (24), or inducible in vivo during colonic inflammation (25) or in vitro by cytokines (21) or in response to infection with invasive bacteria (22,26).…”
mentioning
confidence: 99%
“…These chemokines can attract and activate neutrophils and monocytes/macrophages, which are important components of the acute inflammatory response initiated after enteric infection with invasive bacteria. Other epithelial genes induced after infection with invasive bacteria include cyclooxygenase-2, one of the crucial rate-limiting enzymes for prostaglandin production, and inducible NO synthase, which controls NO production (7)(8)(9). These genes are induced after infection with very different invasive bacteria, which have unique invasion strategies and reside in different intracellular compartments (1,10).…”
mentioning
confidence: 99%